Bactericidal test of endotoxin crystal extract of Bacillus thuringiensis israelensis (H-14) on the larvae of aedes aegypti, Anopheles aconitus and Culex quinquefasciatus - Yusnita Mirna Anggraeni; Blondine Christina P; Rendro Wianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Bacillus thuringiensis israelensis (H-14) has been known as toxin-forming biolarvacide (ä-endotoxin) which effectively kills the larvae of Aedes aegypti, Anopheles aconitus and Culex quinquefasciatus. The crystal of ä-endotoxin is target specific and has high toxicity to the organism of target. The objective of the study was to obtain the crystal of ä-endotoxin by extracting it from Bt (H-14) which is able to kill the larvae of Ae. aegypti, An. aconitus and Cx. quinquefasciatus. The research was conducted in the Laboratory of Microbiology Research Center for Disease Vector and Reservoir Salatiga for nine months in 2010. The lethal concentration (LC) value of ä-endotoxin against the larvae of Ae. aegypti, An. aconitus and Cx. quinquefasciatus respectively were 0.06 (LC50 ); 0.17 ppm (LC90 ); 0.21(LC50 ); 0.49 ppm (LC90 ); 3.58 (LC50 ) and 9.19 ppm (LC90 ).